Integrating Digital Tools and Artificial Intelligence to Enhance Communicative Competence in University EFL Classrooms - Bekchanova, Intizor (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
The rapid advancement of digital technologies and artificial intelligence (AI) has transformed the field of education, particularly in English as a Foreign Language (EFL) instruction. This study investigates the impact of integrating digital tools and AI-based applications on the development of communicative competence among university students. The research was conducted at Mamun University with 45 undergraduate EFL learners over one semester. Students were engaged in a blended learning model that incorporated AI-powered writing assistants, interactive speaking platforms, and digital collaboration tools. Pre- and post-assessment results, supported by qualitative feedback, revealed notable improvements in students’ fluency, accuracy, and motivation to communicate in English. The findings suggest that strategic use of technology not only enhances linguistic outcomes but also promotes learner autonomy and engagement. Implications for EFL teachers and recommendations for further research are discussed.